The Effect of Environmental Performance, Environmental Costs, Carbon Emission Disclosure on Financial Performance and Value of Property and Real Estate Companies in the Period 2022-2024 - Bagas Tirta Syech Maulana; Banu Witono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of environmental performance, environmental costs, and carbon emission disclosure on financial performance and firm value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative approach was employed using secondary data obtained from annual and sustainability reports. The research sample was selected through purposive sampling based on the availability and completeness of relevant data. Financial performance was measured using Return on Assets (ROA), while firm value was proxied by Tobin’s Q. Environmental performance was assessed through ISO 14001 certification, environmental costs were calculated as the proportion of corporate social responsibility expenditure to profit, and carbon emission disclosure was measured using a dichotomous disclosure index. Data were analyzed using multiple linear regression, supported by descriptive statistics and classical assumption tests. The findings indicate that environmental performance has a positive effect on financial performance, while environmental costs negatively affect financial performance. Carbon emission disclosure does not significantly influence financial performance. Regarding firm value, environmental performance and environmental costs show no significant effect, whereas carbon emission disclosure positively influences firm value, suggesting that investors increasingly value transparency related to environmental impacts. These results highlight the differing roles of environmental initiatives in shaping corporate financial outcomes and market valuation.